Pengaruh kepuasan kerja, lingkungan kerja dan efikasi diri terhdapa komitmen organisasi di rumah sakit smc samarinda - Muhammad Iqbal Zainal Abidin; Yonathan Pongtuluran; Siti Maria (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this study was to determine the influence of job satisfaction, the work environment and self efficacy on commitmen organizational. This research was conducted at the hospital SMC Samarinda sampling method using census sampling and purposive sampling, collected samples of 105 nurse. The data in this study using primary data, interviews and questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 20. The results of this study show that: 1) Job satisfaction has a positive and significant effect on commitment organizational in hospital SMC Samarinda, 2) The work environment has a positive and significant effect on commitment organizational in hospital SMC Samarinda, 3) Self efficacy has a positive and significant effect on commitment organizational in hospital SMC Samarinda.Keyword: Job satisfaction, the work environment, self efficacy, and commitmen organizational